Oral cancer in South East Asia: Current status and future directions. (18th April 2017) - Cheong, Sok Ching; Vatanasapt, Patravoot; Yi-Hsin, Yang; Zain, Rosnah B; Kerr, Alexander Ross; Johnson, Newell W
Objectives: To document the burden of oral cancer in South East Asia (SEA) and to examine the gaps in acquiring accurate data within these countries. Methods: Epidemiological data on oral cancer from countries in SEA were obtained and reviewed from public population-based databases. Descriptions on the incidence and mortality of oral cancer were based on data obtained from GLOBOCAN 2012, and prediction of the number of cases and deaths due to oral cancer were also taken from the same database. The availability of and accessibility to population-based cancer registry were also documented. Results: Five of the eleven countries in SEA have national cancer registries, but the reporting periods varied from 2002 to 2014 across these countries. Whilst incidence and mortality data were obtainable for all SEA countries from GLOBOCAN 2012, data quality varied substantially across the countries. Estimated incidences of oral cancer ranged from 1.6 to 8.6/100, 000 per annum with similar rates in males and females for most countries. The incidence was the highest in Myanmar and Brunei for males and females, respectively. Mortality due to oral cancer was reported to be 0.4 to 5.3/100, 000, with the highest mortality in Myanmar and Timor-Leste among males and females, respectively. Based on the predicted number of cases and deaths for 2020, oral cancer incidence and mortality is expected to increase and the trends are similar between males and females, which is not surprising as with population growth, the disease burden will rise further. Conclusion: This study demonstrates a severe lack of accurate epidemiological data on oral cancer and underscores the urgent need to develop expertise within this region that can address this issue. While there is a clear need for improved primary prevention, for increased skilled workforce and for improved diagnostic and treatment facilities, an essential first step is to establish robust cancer registries so that progress or lack thereof can be monitored accurately, and appropriate action planned.